Body of water - Dooley, Sarah (Feiwel and Friends, 2011)
After their trailer home and all their belongings are burned, twelve-year-old Ember and her Wiccan family move to a lakeside campground where Ember's anguish over losing her dog, as well as her friendship with the boy she fears started the fire, stops her from making new friends and moving on